Hubungan Jenis Kelamin, Persepsi Citra Tubuh, dan Penggunaan Media Sosial Dengan Body Dysmorphic Disorder Pada Remaja di SMA X Mataram - Ida Bagus Ari Satya Daniswara; Lusiana Wahyu Ratna Wijayanti; Nisia Putri Rinayu; Dewi Utary (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Body Dysmorphic Disorder (BDD) is a psychological disorder characterized by excessive preoccupation with perceived physical flaws that are minimal or not objectively observable. Factors presumed to contribute to BDD include gender, body image perception, social media use, and bullying. Objective to determine the relationship between gender, body image perception, and social media influence with the incidence of Body Dysmorphic Disorder among adolescents at SMA X Mataram. This study employed a cross-sectional design using a cluster sampling technique with a total of 103 respondents. Data were analyzed using univariate and bivariate methods, with the Spearman’s Rank test applied for correlation analysis. The findings showed a significant relationship between gender and the level ofBody Dysmorphic Disorder (BDD) (p- value = 0.013), a significant relationship between body image perception and BDD (p-value = 0.000), and a significant relationship between social media use and BDD (p-value = 0.003). There is a significant association between gender, body image perception, and social media use with the level of Body Dysmorphic Disorder among adolescents. These findings indicate that BDD is a multifactorial condition influenced by the interaction of various contributing factors. Keywords: Body Dysmorphic Disorder (BDD), Gender, Body Image Perception, Social Media Use.  ABSTRAK Body Dysmorphic Disorder (BDD) merupakan gangguan psikologis yang ditandai dengan preokupasi berlebihan terhadap kekurangan fisik yang bersifat minimal atau tidak tampak secara objektif. Faktor yang berperan meliputi jeniskelamin, persepsi citra tubuh, penggunaan media sosial, dan bullying. Tujuan untuk mengetahui hubungan jenis kelamin, persepsi citra tubuh, dan pengaruh media sosial dengan kejadian Body Dysmorphic Disorder pada remaja di SMA X Mataram. Penelitian ini menggunakan desain cross-sectional dengan teknik cluster sampling pada 103responden. Analisis data dilakukan secara univariat dan bivariat menggunakan uji Spearman’s Rank. Hasil penelitian menunjukkan terdapat hubungan signifikan antara jenis kelamin dengan tingkat Body Dysmorphic Disorder (BDD) (p-value 0,013), terdapat hubungan signifikan antara persepsi citra tubuh dengan tingkat BDD (p-value 0,000), serta terdapat hubungan signifikan antara penggunaan media sosial dengan tingkat BDD (p-value 0,003). Terdapat hubungan yang signifikan antara jenis kelamin, persepsi citra tubuh, dan penggunaan media sosial dengan tingkat Body Dysmorphic Disorder (BDD) pada remaja. Temuan ini menunjukkan bahwa BDD merupakan kondisi multifaktorial yang dipengaruhi oleh interaksi berbagai faktor. Kata Kunci: Body Dysmorphic Disorder (BDD), Jenis Kelamin, Persepsi Citra Tubuh, Penggunaan Media Sosial.